2016
DOI: 10.5194/se-7-1405-2016
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric influence on the seismo-telluric current related to electromagnetic signals observed before the Wenchuan <i>M</i><sub><i>S</i></sub> 8.0 earthquake

Abstract: Abstract. A three-layer (Earth-air-ionosphere) physical model, as well as a two-layer (Earth-air) model, is employed in this paper to investigate the ionospheric effect on the wave fields for a finite length dipole current source co-located at a hypocenter depth and along the main fault of an earthquake when the distance between the epicenter and an observing station is up to 1000 km or even more. The results show that all electrical fields are free of ionospheric effects for different frequencies in a relativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 52 publications
(65 reference statements)
1
9
0
Order By: Relevance
“…Many researchers have investigated the EM effects since the occurrence of the Wenchuan MS 8.0 EQ on 12 May 2008. These studies were mainly based on the ground-based ultra low frequency / extremely low frequency (ULF-ELF) EM data [32,[34][35][36][37][38][39][40][41] and DC-ULF geomagnetic data [42][43][44][45][46][47][48][49][50][51].…”
Section: Ground-based Electromagnetic Anomaliesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have investigated the EM effects since the occurrence of the Wenchuan MS 8.0 EQ on 12 May 2008. These studies were mainly based on the ground-based ultra low frequency / extremely low frequency (ULF-ELF) EM data [32,[34][35][36][37][38][39][40][41] and DC-ULF geomagnetic data [42][43][44][45][46][47][48][49][50][51].…”
Section: Ground-based Electromagnetic Anomaliesmentioning
confidence: 99%
“…Li et al [32,40,41] reported the outstanding electrical emissions which occurred at the Hebei ULF (0.1-10 Hz) EM observing network in northern China during the Wenchuan M S 8.0 EQ. The Hebei EM observing network was established during 1980s around the area of Beijing in northern China after the occurrence of the Tangshan M S 7.8 EQ on 28 July 1976.…”
Section: Anomalous Emissions On the Ulf-elf Electrical Fieldmentioning
confidence: 99%
“…Lu J et al (2016) have reported that there are a 6.7% negative apparent resistivity anomaly at Pixian station (CD station here in Figure 2) before the Wenchuan EQ and coseismic changes of -0.61% at this station. suggested that the main rupture developed rapidly over the three days before the main shock, producing a strong seismo-telluric current that propagated mainly along the Longmenshan fault; Li M et al (2016) have similarly interpreted the observable 1.3 mV·m -1 electrical field at f = 1 Hz at Gaobeidian station, 1440 km away from the Wenchuan epicenter, using an ionospheric influence physical model. The three-layer model employed here, in our analysis, has also been proposed as a partial explanation of the geomagnetic daily variation observed.…”
Section: Discussionmentioning
confidence: 90%
“…The top medium (ionosphere: z < -100 km) is characterized by electrical properties μ -1 , ε -1 and σ -1 (10 -5 S·m -1 ). More details can be found in Li M et al (2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation